Podcasting in the Post-Broadcast Age: A Systematic Analysis of Transformation, Platformization, and Human Experience - Desmalinda Desmalinda; Fatma Nuraini Zahra (Universitas Ahmad Dahlan, 2026)
According to Nielsen, podcast listening in Indonesia grew to over 3.6 million, with weekly episode consumption increasing by 10%. Podcasts have become popular among younger audiences due to their on-demand nature, diverse content, and personalized experience. This study analyzes the global transformation of podcast use between 2019 and 2024 as part of the evolving media landscape in the post-broadcast age. Using a systematic literature review and descriptive-qualitative analysis on 48 articles, the findings reveal that podcasts have developed in an interdisciplinary manner, functioning not only as entertainment but also as tools for education, journalism, the representation of marginalized communities, and platform-based economic strategies. Importantly, podcasts reshape human experience by fostering intimate listening cultures, participatory communities, digital literacy practices, and new forms of socio-cultural engagement. The results highlight the significant social, cultural, and political implications of podcasts, ranging from community empowerment and digital literacy to the challenges posed by the dominance of global platforms. The study suggests the need for policies to establish a regulatory framework that supports the local podcast ecosystem.